Implementation of School Operational Assistance Fund Management in Improving the Quality of Education in Madrasah Ibtidaiyah - Ara Hidayat; Muhamad Luqman Nuryana; Amanah Amnun Zulfa; Asya Dwina Luthfia (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2025)
Objectives: This study aimed to analyze the implementation of School Operational Assistance (Bantuan Operasional Sekolah, BOS) fund management in improving the quality of education at madrasah ibtidaiyah (Islamic elementary schools in Indonesia), and to identify the challenges and solutions in its implementation. Method: This qualitative descriptive study was conducted at MIN 1 Bandung City. The research subjects included the Principal of Madrasah as a key informant, treasurer, and teacher using the snowball sampling technique. Data were collected through observation, interviews, and documentation, with source triangulation to ensure data validity. Data analysis was carried out through data reduction, data presentation, and conclusion drawing based on cross-verification from various sources. Results: The management of BOS funds at MIN 1 Kota Bandung is conducted through structured planning aligned with the National Education Standards, emphasizing efficiency, transparency, and stakeholder collaboration. Supervision involves school committees and internal auditors to ensure accountability. This management supports educational quality through academic programs, facility improvements, and teacher development. Despite challenges like limited budgets and strict regulations, they were addressed with strategic planning and alternative funding. Contribution of theory: The study also highlights Islamic values such as amanah (trustworthiness), mas'uliyyah (responsibility), shiddiq (honesty), tabligh (transparency), and itqan (professionalism), which reinforce integrity in financial practices. Findings support the Shariah-based education finance model that prioritizes planning, transparency, and accountability. Recommendations: However, since the study focused on one madrasah, broader research across different regions is recommended to validate and generalize the results.